The The differences in Biological, Chemical and Physical Qualities of Well Water In Various Soil Textures in Tegalsari, Banyuwangi - indar aning saputri; joko waluyo; mochammad iqbal (Program Studi Pendidikan Biologi, FKIP Unpas,, 2018)
Water is a natural resource which is needed for his life by all sentient beings is therefore important to know the quality of the water before consumption. The condition and texture of soil can affect the quality of the water. In district of Tegalsari Banyuwangi Regency that has a textured ground clay loam and loam water murky conditions, smelling the salty taste while in other regions the same in the sandy loam textured soil condition the water crystal clear, odorless and not felt. This research was conducted to find out the difference in the quality of biology, chemistry and physics there is ground water well textured clay loam, loam and sandy loam. Water quality test using 3 parameters i.e. biological parameter using the method of the test chemical, MPN includes the measurement of pH, and DO, test of physics include the measurement of TDS and organoleptic color, smell and taste. Research results based on biological and chemical parameters showed that water wells on the land of textured clay loam, loam and sandy loam worthy for consumption, while based on physical parameters (TDS) water well on clay loam textured soil proved to be not worth value consumed with TDS > 500 mg/l. In organoleptik water wells are fit to be consumed is water wells on the land of textured sandy loam because the water is colorless, odorless and tasteless No. The entire research results have been adjusted to PERMENKES RI No. 492/MENKES/PER/IV/2010.